Nilai-nilai Pendidikan Akhlak Dalam Film 172 Days - Nadila Putia Komala Sari (UNISBA Press, 2024)
Abstract. 172 Days is an Indonesian drama film that was first released in 2023. The movie is based on the novel of the same name by Nadzira Shafa. The movie tells the story of Nadzira Shafa, a young woman who decides to go on a spiritual journey to find herself. She chooses to live a more religious life and meets Ameer, a young religious teacher. Based on this phenomenon, the problems in this study are formulated as follows: (1) What are the moral education values contained in the movie 172 Days? (2) What moral messages can be taken from the movie 172 days? Research like this is included in the category of descriptive qualitative research that uses a semiotic approach. Descriptive qualitative analysis is the process of collecting data systematically, dividing data into relevant categories, and analyzing the results. Qualitative research gives researchers the confusion to change the focus of their research according to new findings. This allows researchers to dig deeper into certain aspects that they consider important or interesting. The data collection technique used in this research is watching the movie 172 Hari carefully and recording scenes that contain moral values, Collecting data from related sources, such as film scripts, reviews, and additional relevant literature The data analysis technique used in this research is the semiotic analysis technique used in this research. Semiotics is used as a model for understanding the world as an interconnected system with units of measurement known as signs. In this way, semiotics teaches the nature of the location of a particular object. A sign is a material object with a physical form that can first be perceived by the five senses, but also has an influence on the objects that are under it and hinders its use, hence the term